MENEROPONG MUSLIM SIEM REAP DI KAMBOJA - Nanda Khairiyah (Prodi Tasawuf dan Psikoterapi, Fakultas Agama Islam, Universitas Muhammadiyah Cirebon, 2020)
The research based on author’s interest about the growth of Islam community as minority in Siem Reap, Cambodia. Siem Reap is a popular and interested place for tourism in South East Asian while not for Indonesian. Speaking about Siem Reap is not only about tourism, it is more about dark history of Khmer Kingdom and also history about Muslim Cham-Chvea as Islam population in Cambodia. The Cham-Chvea who was founded in the time writer do the research has a common history to Indonesian Islam Population. That is why author thinks that Islam growth in Siem Reap, Cambodia has the same root as Indonesian.